PENYULUHAN PENANAMAN DAN PEMANFAATAN TANAMAN OBAT KELUARGA (TOGA) SEBAGAI JAMU TRADISIONAL MASYARAKAT DESA SENGKOL - Ichfa, Muhammad Syach Maulad; Maulana, Farreh Alan; Utami, Ni Wayan Putri; Handayani, Ervina; Fitriani, Fitriani; Hikmaturrohmi, Hikmaturrohmi; Haqiqi, Nirwana; Saraswati, Putu Bella Aprillia; Nurhidayati, Siti Zainiah; Qoriasmadillah, Wanda; Arrazy, Mu'adz; Ramadhan, Moch. Fitrah; Prasedya, Eka Sunarwidhi (Jurnal Abdi Insani, 2024)
Indonesia is a country rich in natural resources with 30,000 species of plants that have the potential as medicines from a total of 40,000 plant species in the world. Most Indonesians have home yards, but still few are managed productively by planting TOGA. The large area, the large number of hamlets, and the dense population cause various problems in Sengkol Village, one of which is the lack of understanding about the importance of planting and utilizing TOGA. Therefore, it is necessary to conduct counseling on the importance of planting TOGA in the yard and demonstration of the use of TOGA into traditional herbal medicine as an alternative treatment with low costs and low side effects. Counseling and demonstrations in this activity are carried out by lecture and discussion methods, as well as product demonstrations. The lecture method is carried out when delivering counseling materials, the discussion method is carried out during the question and answer session, and the product demonstration method is carried out when demonstrating the making of herbal medicine from TOGA. The location of TOGA planting was carried out on an empty land in the yard of one of the residents of Pampang Lauk Hamlet with a land size of 6x6 m2. TOGA that is planted has properties that are adapted to diseases that commonly occur in the community, namely yellow turmeric, white turmeric, ginger, ginger, galangal, kencur, katuk, virgin palm, lemongrass, betel. Making a green house was carried out for one week involving youth and villagers using bamboo and paranets. Counseling participants were dominated by men (66.6%), adolescents (57.57%), and students (42.42%). The material presentation, discussion, and demonstration sessions went smoothly and the community was very enthusiastic about participating in the activity. Based on the counseling that has been carried out, the urgency of planting TOGA in the yard and the use of TOGA as an alternative treatment is well conveyed.